A computed tomography-based nomogram for neoadjuvant chemotherapy plus immunotherapy response prediction in patients with advanced esophageal squamous cell carcinoma - Guo, Wen-wen; Zhou, Chuanqinyuan; Gao, Dan; Xu, Min; Gui, Yan; Zhou, Hai-ying; Chen, Tian-wu; Zhang, Xiao-ming (Frontiers in Oncology, 2024)
Objective: To develop a CT-based nomogram to predict the response of advanced esophageal squamous cell carcinoma (ESCC) to neoadjuvant chemotherapy plus immunotherapy. Methods: In this retrospective study, 158 consecutive patients with advanced ESCC receiving contrast-enhanced CT before neoadjuvant chemotherapy plus immunotherapy were randomized to training cohort (TC, n = 121) and validation cohort (VC, n = 37). Response to treatment was assessed with response evaluation criteria in solid tumors. Patients in TC were divided into responder (n = 69) and non-responder (n = 52) groups. For TC, univariate analyses were performed to confirm factors associated with response prediction, and binary analyses were to identify independent variables to develop a nomogram. In both TC and VC, the nomogram performance was assessed by area under the receiver operating characteristic curve (AUC), calibration slope and decision curve analysis (DCA).In TC, univariate analysis showed that cT stage, cN stage, gross tumor volume, gross volume of all enlarged lymph nodes, and tumor length were associated with the response (all P < 0.05). Binary analysis demonstrated that cT stage, cN stage, and tumor length were independent predictors. The independent factors were imported into the R software to construct a nomogram, showing the discriminatory ability with an AUC of 0.813 (95% confidence interval: 0.735-0.890), and the calibration curve and DCA showed that the predictive ability of the nomogram was in good agreement with the actual observation.This study provides an accurate nomogram to predict response of advanced ESCC to neoadjuvant chemotherapy plus immunotherapy.